Defining Aesthetic Preferences for the Penis: A Photogrammetric and Crowdsourcing Analysis. (11th February 2021) - Massie, Jonathan P; Sood, Rachita; Nolan, Ian T; Sasson, Daniel C; Swanson, Marco; Morrison, Shane D; Placik, Otto
Abstract: Background: Achieving an aesthetic phalloplasty result is important for patients with acquired or congenital defects of the penis, or with genital-related dysphoria. However, aside from length and girth, the aesthetic proportions of the male penis have not been defined. Objectives: This study aimed to determine proportions of the male penis through photogrammetric analysis of nude male photographs and to verify these proportions with a crowdsourcing-based survey. Methods: Nude male photographs (n = 283) were analyzed to define aesthetic proportions of the male penis. Photographs were analyzed for the position of the penis on the torso in relation to the umbilicus and for the ratio of the dorsal and ventral glans of the penis in relation to the entire shaft length. Proportions were then further studied by crowdsourcing 1026 respondents with Amazon mechanical Turk. Results: The ideal position of the penis below the umbilicus is about 55% (6/11th) of the distance from the jugular notch to the umbilicus (measured average, 53.6%; survey-weighted average, 58.9%). The dorsal glans of the penis is about 33% (1/3rd) of the length of the entire shaft (measured average, 32.1%; survey-weighted average, 37.5%). The ventral glans of the penis is about 12.5% (1/8th) of the length of the entire shaft (measured average, 12.6%; survey-weighted average, 11.7%). Conclusions: Measured proportions of the human penis follow exact fractions. Crowdsourcing data helped support photogrammetric analysis, with survey-preferred ratios within 5% of measured ratios. With further validation, these data can aid surgeons performing phalloplasty.